Taxonomic implications of geographical variation in Rhinolophus affinis (Chiroptera: Rhinolophidae) in mainland Southeast Asia - Saveng, Ith; Sara, Bumrungsri; Neil M, Furey; Paul JJ, Bates; Faisal Ali, Anwarali Khan (Springer Berlin Heidelberg, 2015)
Background